Choosing the Right Pest Control Operator for Honey Bee Removal: A Consumer Guide - Michael K. O'Malley; James D. Ellis (EDIS)
ENY-144, a 6-page illustrated fact sheet by M. K. O’Malley and J. D. Ellis, guides Florida resident in ensuring that the honey bees on his or her property are safely and professionally removed. Includes additional resources of information. Published by the UF Department of Entomology and Nematology, September 2008.